Investigation of structure-directing interactions within copper(i) thiocyanate complexes through X-ray analyses and non-covalent interaction (NCI) theoretical approach. Issue 37 (30th August 2016) - Gholivand, Khodayar; Farshadfar, Kaveh; Roe, S. Mark; Hosseini, Mahdieh; Gholami, Akram
Abstract : Structure-directing interactions within copper(i ) thiocyanate carbohydrazone derivatives were discussed in terms of geometrical parameters and the NCI-RDG approach. Abstract : Herein, we reported the synthesis of copper(i ) thiocyanate complexes with ortho -pyridinyl carbohydrazones containing a thiophene (L 1 ) or a furyl ring (L 2 ) as a mixture of two different crystals for each compound, linkage isomers ofC1N, [Cu(NCS)(L1 )PPh3 ] andC1S, [Cu(SCN)(L1 )PPh3 ], forL 1, whereas monomeric and polymeric structuresC2N, [Cu(NCS)(L2 )PPh3 ], andC2P, [–(NCS)Cu(L2 )–] n, forL 2 . Crystallographic information and theoretical calculations, mainly noncovalent interaction reduced density gradient (NCI-RDG) analyses, were pursued to generate a profound understanding of the structure-directing interactions in these complexes. The supramolecular assemblies are first driven by cooperative π⋯π interactions and hydrogen bonds followed by CH⋯π, S⋯S and S⋯π linkages. In the case of the linkage isomers, intermolecular interactions may have a significant role in the formation of the less stable S-bound isomerC1S .